Crisis Preparedness and Debt Management in Low Income Countries : Strengthening Institutions and Policy Frameworks - Weist, Dana (2012)
The magnitude of the public liabilities incurred as a result of the unprecedented government action in the wake of the financial crisis of 2008-2009, and the consequences of exiting from the projected high debt scenario, have become a major source of concern about a future sovereign debt crisis. As Low-Income Countries (LICs) face unique challenges in debt management (DeM) due to their more limited financing sources and higher capacity constraints, their ability to successfully manage their public debt burdens effectively through a crisis of this magnitude is far from assured. Therefore, the challenges of the last two years will require a re-evaluation of existing DeM strategies in LICs, focusing on the identification of institutional weaknesses and the assessment and mitigation of potential risk. It is in this context that this paper examines the application of two global public goods in LICs: the Debt Management Performance Assessment (DeMPA) and the Medium-Term Debt Management Strategy (MTDS) tools. The results of the application of these tools from 2007-2009 provide valuable information to policymakers and other stakeholders on the development of sound public DeM practices and analytical capacity, with the goal of strengthening the public balance sheet and reducing vulnerability to financial crises.